2009
DOI: 10.1159/000236000
|View full text |Cite
|
Sign up to set email alerts
|

Oral Treatment with Probiotics Reduces Allergic Symptoms in Ovalbumin-Sensitized Mice: A Bacterial Strain Comparative Study

Abstract: Background/Aim: Evidence demonstrating an important role of the intestinal microbiota in the incidence of allergic disorders has led to the concept of using probiotics as possible antiallergic therapy. This study aimed to select a bacterial strain with the best antiallergic treatment effects from a panel of 6 bacterial strains in a mouse model of ovalbumin(OVA)-allergic asthma. Methods: OVA-sensitized BALB/c mice were orally administered the bacterial strains Bifidobacterium breve M-16V, B. infantis NumRes251,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
85
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(94 citation statements)
references
References 76 publications
3
85
1
5
Order By: Relevance
“…Animal studies suggest that the effects of probiotics on allergeninduced airway responses may be sensitive to the organism used: L reuteri, but not Lactobacillus salivarius, has been shown to inhibit allergic airway responses in sensitized mice, 51 and a recent study by Hougee et al 54 demonstrated Bacillus brevis has strain-dependent immunomodulatory effects. The duration and timing of feeding are also determinants of antiinflammatory efficacy; Forsythe et al 51 found that a period of feeding of at least 9 days was required for significant inhibition of airway eosinophilia and airway hyperreactivity in mice.…”
Section: Figurementioning
confidence: 99%
“…Animal studies suggest that the effects of probiotics on allergeninduced airway responses may be sensitive to the organism used: L reuteri, but not Lactobacillus salivarius, has been shown to inhibit allergic airway responses in sensitized mice, 51 and a recent study by Hougee et al 54 demonstrated Bacillus brevis has strain-dependent immunomodulatory effects. The duration and timing of feeding are also determinants of antiinflammatory efficacy; Forsythe et al 51 found that a period of feeding of at least 9 days was required for significant inhibition of airway eosinophilia and airway hyperreactivity in mice.…”
Section: Figurementioning
confidence: 99%
“…Oral administration of B. breve to mice with IgE-mediated hypersensitivity to cow milk or ovalbumin promotes a significant improvement in allergic symptoms (9,10). Although B. breve influences bacterial colonization in the intestine and enhances TGF-β1 signaling by regulating Smad7 expression in preterm infants (11,12), the precise mechanisms of these interactions have not been well established.…”
mentioning
confidence: 99%
“…Gene expression in the rat colon, small intestine, and spleen was examined by microarray and real-time PCR after feeding 5 × 10 8 colony-forming units/animal B. breve to rat pups during the newborn (days [1][2][3][4][5][6][7][8][9][10][11][12][13][14] or weaning (days 21-34) period.…”
mentioning
confidence: 99%
“…Oral treatment with probiotics reduces allergic symptoms in ovalbumin-sensitized mice [62]. Perinatal Lactobacillus rhamnosus GG (LGG) supplementation has beneficial effects on the development of allergic asthma in offspring [63].…”
Section: Effects On Inflammatory Cells and Cytokinesmentioning
confidence: 99%